Excel 2007 formulas - Walkenbach, John (Wiley Pub., 2007)
Create killer formulas--Mr. Spreadsheet shows you how Excel master John Walkenbach has shared his expertise in two previous editions of this bestseller. Now he shows you how to create financial formulas, release the power of array formulas, develop custom worksheet functions with VBA, debug formulas, and more with Excel 2007